Non-alcoholic fatty liver disease in Africa: a hidden danger. (2019) - Paruk, Imran M.; Pirie, Fraser J.; Motala, Ayesha A.
Abstract: There is a dearth of data on the burden and spectrum of non-alcoholic fatty liver disease (NAFLD) in African populations. The limited available information suggests that the prevalence of NAFLD in the general population is lowest for the Africa region. However, this is likely to be an underestimate and also does not take into consideration the long-term impact of rising rates of obesity, type-2 diabetes mellitus (T2DM) and high human immunodeficiency virus infection burden in Africa. A racial disparity in the prevalence of NAFLD has been observed in some studies but remains unexplained. There is an absence of data from population-based studies in Africa and this highlights the need for such studies, to reliably define the health service needs for this region. Screening for NAFLD at a population-based level using ultrasound is perhaps the ideal method for resource-poor settings because of its relative cost-effectiveness. What is required as a priority from Africa, are well-designed epidemiologic studies that screen for NAFLD in the general population as well as high-risk groups such as patients with T2DM or obesity.